Leiomyosarcoma of the renal pelvis - Dhamne Sagar; Gadgil Nitin; Padmanabhan Anita (Wolters Kluwer Medknow Publications, 2009)
Leiomyosarcomas are rare malignant tumors of the kidney. They may arise from the renal capsule, renal vein, renal pelvic musculature or renal parenchyma. Renal pelvis is an uncommon site of occurrence, with around 10 cases reported in the literature so far. Here we present a 60-year-old male who presented with increased urinary frequency, lower limb weakness, anorexia and weight loss. Imaging showed a right renal mass. A renal cell carcinoma was suspected clinically. A right nephrectomy was performed, which showed a large circumscribed mass in the hilar region. Histology revealed a tumor mass arising from the renal pelvis. The tumor was composed of spindle cells arranged in fascicles. Immunohistochemistry showed tumor cells to be positive for smooth muscle actin (SMA) and desmin (Des) and negative for cytokeratin (CK), HMB 45, CD117 (C-kit), and CD34. That confirmed the diagnosis of leiomyosarcoma.